Implementasi Strategi Pembelajaran Inquiry pada Mata Pelajaran Akidah Akhlak di MTs Pondok Pesantren Modern Darul Hikmah TPI Medan - Arlina, Arlina; Putri, Ayilzi; Aisyah, Nurul; Pratama Siregar, Alde Rizky (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to involve students directly in the learning process of Class VII students at MTs Islamic Boarding school Modern Darul Hikmah TPI Medan through the application of inquiry-based learning strategies to instill scientific skills and motivate students. This research uses qualitative methods with a phenomenological approach. The data collection methods used were interviews, observation, documentation and group discussions. Class VII students were participants in this research. The data analysis method in this research was carried out from pre-field implementation to completion in the field. Data validation was carried out using source triangulation. The data analysis used uses Hyberman's opinion, namely data reduction activities or making reports from start to finish which selects basic data found in the field, presents the data, reviews incomplete data, and finally draws conclusions. From the results of observations and interviews conducted by the author, it is known that the application of inquiry learning strategies increases students' learning motivation and increases their learning motivation.